Endothelial cell metabolism in health and disease: impact of hypoxia. (21st June 2017) - Wong, Brian W; Marsch, Elke; Treps, Lucas; Baes, Myriam; Carmeliet, Peter
Abstract: In contrast to the general belief, endothelial cell (EC) metabolism has recently been identified as a driver rather than a bystander effect of angiogenesis in health and disease. Indeed, different EC subtypes present with distinct metabolic properties, which determine their function in angiogenesis upon growth factor stimulation. One of the main stimulators of angiogenesis is hypoxia, frequently observed in disease settings such as cancer and atherosclerosis. It has long been established that hypoxic signalling and metabolism changes are highly interlinked. In this review, we will provide an overview of the literature and recent findings on hypoxia‐driven EC function and metabolism in health and disease. We summarize evidence on metabolic crosstalk between different hypoxic cell types with ECs and suggest new metabolic targets. Abstract : The metabolic and hypoxic signaling pathways acting in vascular endothelial cells, and impacting on conditions such as cancer and atherosclerosis, are the focus of this part of our Metabolism review series.